Sonographic Assessment of Hepatic Steatosis (Fatty Liver) in< School Children of Dera Ismail Khan City (NWFP) Pakistan - Ramzan, M.; Ali, I.; Matin, A. (Pakistan Journal of Nutrition, 2009)
Childhood obesity is escalating rapidly, both in industrialized and developing countries. It will emerge as a potential public health burden faced by the developing countries in the near future. In children, Non Alcoholic Fatty Liver Disease (NAFLD) is mainly associated with obesity and metabolic syndrome and is therefore considered as a metabolic complication of obesity. NAFLD comprises of a range of chronic liver diseases from simple steatosis, steatohepatitis and cirrhosis with liver failure. Since the prevalence of obesity in children is increasing, the prevalence of NAFLD in children is expected to increase as well. Prevention of obesity and identification of children with an increased risk of NAFLD are important steps in preventing irreversible liver damage. This prospective study was carried out in the primary schools of Dera Ismail Khan History City having mixed population. Clinical examination of the children excluded those suffering from chronic health ailments. History from the parents excluded the intake of hepatotoxic drugs. Body mass status of child was determined according to World Health Organization s' criteria and Centers for Disease Control and Prevention (CDC)'s gender and age specific growth charts. Randomly selected normal weight and obese children have undergone abdominal ultrasound examination to confirm or rule out hepatic steatosis (Fatty Liver) by detecting the alteration in ultrasound/hyperechogenicity of the organ. Randomly selected children (normal weight and obese) among the 1336 school going children were subjected to ultrasound examination, comprising of 55 boys (59.13%) and 38 (40.86%) girls. 67 (72.04%) were obese and 26 (27.95) as normal weights. Hepatic ultrasound alterations/hyperechogenic liver was found in 7 (7.52%) obese boys. None of the obese girls and normal weight children was found to exhibit any alteration in ultrasound findings.